2009
DOI: 10.2174/1874256400903010010
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Production of Nattokinase and Vitamin K2 in Natto with Dipicolinic Acid

Abstract: Abstracts: It was found that when dipicolinic acid is added to the culture solution of Bacillus subtilis natto, the area of fibrin dissolved by nattokinase (standard fibrin plate) and the amidase activity of nattokinase against Suc-Ala-Ala-Pro-PhepNA increased. For example, when manufacturing natto using steamed soybeans, the addition of 10-64 mM of dipicolinic acid increases amidase activity by more than 10 times.The concentration of vitamin K 2 (menaquinone-7) also increased by about 4 times with the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This means that someone who eats nattō ingests this amount of dipicolinic acid on a daily basis [13] . Dipicolinic acid is a kind of chelate substance with some notable characteristics such as promoting the growth of B. subtilis natto and increasing the amounts of nattokinase and vitamin K 2 [14,15] . Hagiwara et al [16] reported that sitosterol and fucosterol work on bovine vascular endothelial cells to help release tPA.…”
Section: Discussionmentioning
confidence: 99%
“…This means that someone who eats nattō ingests this amount of dipicolinic acid on a daily basis [13] . Dipicolinic acid is a kind of chelate substance with some notable characteristics such as promoting the growth of B. subtilis natto and increasing the amounts of nattokinase and vitamin K 2 [14,15] . Hagiwara et al [16] reported that sitosterol and fucosterol work on bovine vascular endothelial cells to help release tPA.…”
Section: Discussionmentioning
confidence: 99%
“…Many different medium components could affect the synthesis of MK-7. These include carbon source, nitrogen source, phosphate source, surfactants, and activators [9,13,[16][17][18]. In preliminary experiments, the medium constituents were optimized by the onefactor-at-a-time (OFAT) method.…”
Section: Experimental Designmentioning
confidence: 99%
“…After 84 hours of fermentation, they achieved a yield of 5.3 g/kg for iturin A and 51.3 g/kg for poly-γglutamic acid.Xu et al(Xu et al 2020) engineered metabolic pathways and optimized conditions to attain an iturin A yield of 2013.43 ± 32.86 mg/L. Hiroyuki Sumi(Sumi et al 2009) introduced dipicolinic acid for co-fermentation, resulting in maximum nattokinase activity at 479 mm 2 /mL with 16 mM dipicolinic acid and a vitamin K2 yield of 3.26 ± 0.09 µg/mL with 10 mM dipicolinic acid in shake ask fermentation. Wang et al(H Wang et al 2018…”
mentioning
confidence: 99%